2012
DOI: 10.1186/1477-3155-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based method for screening of immunogenic proteins from bacteria

Abstract: BackgroundDetection of immunogenic proteins remains an important task for life sciences as it nourishes the understanding of pathogenicity, illuminates new potential vaccine candidates and broadens the spectrum of biomarkers applicable in diagnostic tools. Traditionally, immunoscreenings of expression libraries via polyclonal sera on nitrocellulose membranes or screenings of whole proteome lysates in 2-D gel electrophoresis are performed. However, these methods feature some rather inconvenient disadvantages. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Two highly immunogenic, extracytoplasmic and conserved C. jejuni proteins — CjaA (Cj0982c in the genome of C. jejuni NCTC11168) and CjaD (Cj0113 in the genome of C. jejuni NCTC11168), which are often tested as candidates for chicken anti- Campylobacter vaccination – were chosen for this study. The immunogenicity of CjaA and CjaD has been documented by our research group, as well as by others ( Wyszyńska et al, 2004 ; Buckley et al, 2010 ; Layton et al, 2011 ; Clark et al, 2012 ; Hoppe et al, 2012 ). Recently we have shown that GEM particles (Gram-positive Enhancer Matrix), from TCA-pretreated L. salivarius , can act as a surface display platform for C. jejuni antigens ( Bosma et al, 2006 ; Kobierecka et al, 2015 ).…”
Section: Resultssupporting
confidence: 75%
“…Two highly immunogenic, extracytoplasmic and conserved C. jejuni proteins — CjaA (Cj0982c in the genome of C. jejuni NCTC11168) and CjaD (Cj0113 in the genome of C. jejuni NCTC11168), which are often tested as candidates for chicken anti- Campylobacter vaccination – were chosen for this study. The immunogenicity of CjaA and CjaD has been documented by our research group, as well as by others ( Wyszyńska et al, 2004 ; Buckley et al, 2010 ; Layton et al, 2011 ; Clark et al, 2012 ; Hoppe et al, 2012 ). Recently we have shown that GEM particles (Gram-positive Enhancer Matrix), from TCA-pretreated L. salivarius , can act as a surface display platform for C. jejuni antigens ( Bosma et al, 2006 ; Kobierecka et al, 2015 ).…”
Section: Resultssupporting
confidence: 75%
“…As we have shown elsewhere, an approach using HaloTagH and specifically coated HaloLink TM slides is better suited to detect immunodominant proteins while reducing cross-reactivity to a minimum [13]. The HaloTagH provides several advantages to other commonly used tags as it enhances the amount of soluble proteins expressed [14] reducing the formation of inclusion bodies.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of protein microarrays to identify ligand-binding proteins is an innovative approach (51,60,73,106) that could serve as a useful tool for elucidating host-pathogen interactions. In the microbiology field, proteome microarrays have mostly been used for serological studies to identify targets of the human or animal immune response during course of infection with the goal of discovering diagnostic antigens (6,9,15,22,25,26,42,44,54,59,68,91,94,99,101,107). To date, a few reports have described protein microarrays as a tool to screen for proteins with host ligand-binding capacities, both studies focusing on Streptococcus (32,61).…”
mentioning
confidence: 99%